Acute toxicity study of three type of Nerium.oleander leaves of hexane extract in mice - Alkhayyat, Ali Aziz; Ahmed Kafi‎, Lubna; Ahmed Hatif‎, Zena (The Iraqi Journal of Veterinary Medicine, 2010)
Three types of Nerium.oleander leaves of hexane extract were prepared according the color of their flower, red flower group (RFG), pink flower group (PFG) and white flower group (WFG).After drying in the sunlight, grinding by electrical grinder. Extraction with hexane was done by a soxhlet apparatus for each type the extract of each type was dissolved in propylene glycol which was used to dissolve the extract with the aid of magnetic stirrer mixer for ten minutes. The median lethal dose (LD50) experiment for each type, fifty adult mice of mixed sex were used. They were divided into 5 equal number groups and were given different oral doses as following:-The red flower groups (RFG) received oral doses ranging from 225-425mg⁄Kg ,the pink flower group(PFG) received oral doses ranging from 200-400 mg ⁄Kg while the white flower groups (WFG) received doses ranging from 250- 450 mg⁄ Kg of body weight. The LD50 was calculated by employing probit method and found to be 325mg/kg for the RFG, 300mg/kg for the PFG and 350mg/kg for the WFG respectively. These results indicate that the toxic constituents of the leaves nearly same since there were no significance differences between LD50 of the three types.